Evaluation of The Usability of Virtual Reality as An Educational Tool for Nursing Student Simulators - Cahyani, Gita; Susanti, Raini Diah; Mirwanti, Ristina; Somantri, Irman; Permana, Ryan Hara (Universitas Padjadjaran, 2024)
Technology-based simulation learning methods have great potential to support education for students in the health sector. One of the innovations that can be done is virtual reality. In using virtual reality, paying attention to the quality of virtual reality services to provide learning satisfaction and motivate students to be active in the learning process is essential. VNursLab designed VR as an additional learning media for Padjadjaran University nursing students. Therefore, this study aims to identify nursing students' satisfaction with using VR as a learning media simulator.The method used is pre-experimental quantitative research and a one-shot case study approach. The sampling used in the study was purposive. Eighty-six respondents completed the research by following the VR simulation for 20 minutes and continued filling out the PSSUQ (Post-Study System Usability Questionnaire) questionnaire. The data were analyzed using descriptive analytics by finding the mean value of each aspect of the assessment obtained from the mean of each element of the respondent. The results show that the overall quality of VR VNursLab is good (2.2), with a mean value of system quality (2.3), mean InfoQual (2.21), and IntQual (2.28). Based on these results, VR VNursLab as a learning media with virtual simulation methods has a good quality of use assessment and provides satisfaction with nursing students' use.